Antiageing properties of Damaurone D in Caenorhabditis elegans. (10th July 2018) - Kim, Yong Seong; Han, Young Taek; Jeon, Hoon; Cha, Dong Seok
Abstract: Objectives: This study was conducted to evaluate the longevity potential of damaurone D (DaD), a component of the damask rose, in the animal model Caenorhabditis elegans . Methods: To investigate the effect of DaD on the longevity, lifespan assay was carried out. Fluorescence intensity of transgenic mutants was quantified to test the expression levels of stress proteins. A genetic study using single gene knockout mutants was designed to determine the target genes of DaD. Key findings: DaD prolonged the mean lifespan of wild-type nematodes by 16.7% under normal conditions and also improved their stress endurance under thermal, osmotic, and oxidative stress conditions. This longevity-promoting effect could be attributed to in vivo antioxidant capacity and its up-regulating effects on the expressions of stress-response proteins such as SOD-3 and HSP-16.2. In addition, DaD treatment attenuated food intake, body length, lipofuscin accumulation and age-dependent decline of motor ability. Gene-specific mutant studies showed the involvement of genes such as daf-2, age-1, and daf-16 . Conclusions: These results suggest that DaD has beneficial effects on the longevity, and thus it can be a valuable plant origin lead compound for the development of nutraceutical preparations targeting ageing and ageing-related diseases.